The Agro-Chain Greenhouse Gas Emissions (ACGE) calculator for estimating total GHG emissions associated to a food product - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
This calculator is ready to use and works on a personal computer as well as a mobile phone (both in Microsoft Excel). Full instructions are provided on the first worksheet of the calculator (https://hdl.handle.net/10568/106161)